Performance Audit in Construction Organisations: Relevant Criteria and Analytical Procedures - Amanzholova Bibigul; KarakchievaViktoria (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2019)
Performance audit is becoming increasingly ubiquitous in commercial and business spheres internationally. Due to its important role in promoting efficient organisational and administrative practices, performance audit is becoming a subject more rigorously analised in the academic sphere. This study seeks to develop and test analytical tools of performance audit in Russian construction organisations. We place emphasis on the industry-specific dimensions of information disclosure. We intend to offer a solution to several crucial challenges in the field, which will allow for the development of a comprehensive method to implement analytical procedures. This is done with a view towards obtaining and collating sufficient and adequate audit evidence to help achieve business goals. In order to devise a consistent methodology, first, a link is highlighted between construction industry constraints and performance audit criteria. Second, an algorithm is developed to carry out comparative integrated estimation of performance audit criteria in order to shortlist relevant indicators. Third, the algorithm is tested using financial reporting of selected construction companies, which makes it possible to build a consistent system of performance audit criteria and identify a reliable set of controlled parameters. A profile of practical analytical procedures, performance audit criteria and measurement indicators is formed through financial and performance audit and imbedded statistical methods. Implementing this approach will be seen to close some information gaps commonly found in the reporting data of construction industry, as it links the subject area of performance audit and the objective criteria of effectiveness, efficiency and economy. The findings are presented with reference to existing statistical surveys on construction industry constraints. While recent studies provide a broader picture across construction industry, they do not address its regional aspects. As such, within this study we have carried out estimates of performance indicators for construction companies operating in the Novosibirsk region. The estimates are based on the information available through Professional Market and Company Analysis System. As a result, a system of performance audit criteria is identified in relation to the dimensions of effectiveness, efficiency and economy and a framework of controlled parameters is shaped. The level of disclosure concerning these parameters presented in a company’s reporting is supposed to determine the decisions of stakeholders and potential investors. In consideration of further research, this study highlights that it is necessary to identify and validate performance criteria in view of the fact that only few construction companies are profitable. The mix of qualitative and quantitative analytical procedures demonstrated herein is an effective approach to address the challenges of information integrity assessment. We consider that the most promising aspect of this study is the analysis of how the quality and amount of information disclosed in the reporting of construction companies affects their public image and business activities. This can be seen to have widespread industry and academic applications. Additionally, our approach represents a suitable framework for possible adaptation towards not only other industries, but also further development of the methodological approach itself